2017
DOI: 10.4274/tmsj.2017.04.01.0002
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Electrocardiographic Markers to Predict Ventricular Arrhythmias in Acute Myocarditis Patients

Abstract: Aims: Acute myocarditis is an inflammatory disease of the myocardium and is characterized by a large heterogeneity of clinical presentation. Myocarditis is becoming to be recognized as a contributor to unexplained mortality, and is thought to be a major cause of sudden cardiac death in the first two decades of life. Myocardial inflammation, ion channel dysfunction, electrophysiological and structural remodelling may play important roles in life-threatening arrhythmias. We aimed to investigate the ventricular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Yumurtaci et al evaluated iCEB as an indicator of ventricular arrhythmia in patients with acute myocarditis. The authors reported that iCEB values were signifi cantly higher in the arrhythmia group compared to the non-arrhythmia group (17).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Yumurtaci et al evaluated iCEB as an indicator of ventricular arrhythmia in patients with acute myocarditis. The authors reported that iCEB values were signifi cantly higher in the arrhythmia group compared to the non-arrhythmia group (17).…”
Section: Discussionmentioning
confidence: 95%
“…Studies in different patient populations reported that iCEB indicates the susceptibility to developing malignant ventricular arrhythmia (15)(16)(17). Sivri et al assessed iCEB before and after hemodialysis in 52 patients with end-stage renal disease (ESRD).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, Yumurtacı O et al [16] found that iCEB and heart rate-corrected QT(QTc)/QRS ratio was higher in patients with acute myocarditis who had ventricular arrhythmic episodes compare to uneventful control group. Recently, Ucar FM et al [17] have investigated the balance of ventricular depolarization and repolarization in patients with rheumatoid arthritis by using iCEB.…”
Section: Discussionmentioning
confidence: 97%
“…ECG findings of acute myocarditis may appear as changes in the ST segment or T wave and/or as a pathologic Q wave that may be confused with acute myocardial infarction. 11 , 12 , 13 These findings may be the result of diffuse myocardial inflammation which are associated with conduction abnormalities. However, our study showed that the specific ECG findings in fulminant myocarditis are related to QRS duration rather than ST segment changes.…”
Section: Discussionmentioning
confidence: 99%